The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s10843-016-0190-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional and contextual dimensions of INVs’ alliance partner selection

Abstract: Prior research on the selection of international alliance partners calls for investigation of the potential specificity of selection criteria for evaluating partners for alliances with different objectives or functions. The present study responds to this need and contributes to the development of the field of international entrepreneurship by examining the relation between the alliance function and the criteria chosen. We studied three alliance functions: R&D, production, and marketing. Second, for each allian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Extant research also adopts the knowledge-based view to examine entrepreneurial knowledge of opportunity exploitation (Mejri and Umemoto 2010) and uses the resource-based view and capability theory to reveal the effect of opportunity on building and developing marketing capabilities in internationalizing firms (Kaufmann and Roesch 2012). In addition, some literature examines opportunity in international joint ventures and international alliances (e.g., Haskell, Veilleux, and Béliveau 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Extant research also adopts the knowledge-based view to examine entrepreneurial knowledge of opportunity exploitation (Mejri and Umemoto 2010) and uses the resource-based view and capability theory to reveal the effect of opportunity on building and developing marketing capabilities in internationalizing firms (Kaufmann and Roesch 2012). In addition, some literature examines opportunity in international joint ventures and international alliances (e.g., Haskell, Veilleux, and Béliveau 2016).…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that 27 studies (31%) clearly included US firms as one partner in the alliances (e.g. Haskell et al, 2016;Aharonson et al, 2016;Choi & Contractor, 2016).…”
Section: Geographical Coveragementioning
confidence: 99%
“…Analysis of the formation stage is essential since various problems that apply to international SME alliances have often been reported during the initial stage (Lu & Beamish, 2001Nakos & Brouthers, 2008;Swoboda et al, 2011;Shijaku et al, 2020). Of the studies analysed, 53 (62%) focused on the formation stage (Haskell et al, 2016). Partner selection was clearly the most studied aspect, being the focus in 33 (39%) of the studies.…”
Section: Formation Stage Of the Isamentioning
confidence: 99%
“…There are also several studies that confirmed a positive correlation between different CS dimensions and corporate performance. Social dimension can include the corporate responsibility and environmental dimension can include the environmental management systems (Haskell et al , 2016). The causalities between EP and their CS are expected to be positively linked with supported the mediating role of IP and ENs (Martinez-Conesa et al ., 2017).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%